1988
DOI: 10.1111/j.1471-0528.1988.tb12800.x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical artery flow velocity waveforms in fetuses dying with congenital anomalies

Abstract: Summary. Absent or reversed diastolic component in umbilical artery (UA) flow velocity waveform was observed in eight fetuses with major malformations. Because of the uncorrectable fetal conditions or the parents' reluctance to terminate the pregnancy, no interventions were undertaken and eventually all eight fetuses died in utero. The interval between the abnormal waveform recording and fetal death was between 1 and 7 days (mean 3.6 days). In two fetuses with abnormal diastolic flow, analysis of umbilical vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
9

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 19 publications
0
4
0
9
Order By: Relevance
“…The details of these pregnancies are summarized in Table 3. Although previous reports of this finding have shown a close association with fetal and neonatal death (Hsieh et al 1988) all babies but one were born in good condition. The exception had an Apgar score of only 1 at 1 min following cord prolapse and breech extraction; the Apgar score was 7 at 5 min and the baby did well subsequently.…”
Section: Methodsmentioning
confidence: 50%
See 1 more Smart Citation
“…The details of these pregnancies are summarized in Table 3. Although previous reports of this finding have shown a close association with fetal and neonatal death (Hsieh et al 1988) all babies but one were born in good condition. The exception had an Apgar score of only 1 at 1 min following cord prolapse and breech extraction; the Apgar score was 7 at 5 min and the baby did well subsequently.…”
Section: Methodsmentioning
confidence: 50%
“…Forward blood flow in the umbilical artery is normally found throughout the cardiac cycle from early in the second trimester, and absence of end diastolic flow has been associated with severe fetal compromise and high perinatal mortality in pregnancies identified as being at high risk (Hsieh et al 1988;Woo et al 1987). Although this pattern was seen in two pregnancies which resulted in the birth of SGA babies (Table 3), there were no losses.…”
Section: Resultsmentioning
confidence: 99%
“…However, REDFV may be encountered in fetuses with congenital malformations or chromosomal abnormalities (16,24). Hsieh et al (25) have reported seven cases of AEDFV and one case of REDFV with chromosomal or congenital anomalies, which died within 7 days with an average of 3.6 days. Because these abnormal fetuses will die in utero or soon after delivery and the infants born before 28 weeks of gestation are often extremely small with high mortality and morbidity, we need to emphasize and discuss pregnancy outcome in singleton, normal fetuses of more than 28 gestational weeks having REDFV.…”
mentioning
confidence: 99%
“…Feten mit einem ¹Reverse Flowª in der A. umbilicalis und/oder Aorta fetalis stellen eine hochgefährdete Risikogruppe mit erhöhter Mortalität von 35 ± 100 % und erheblicher Morbidität der Neugeborenen dar [1,4,5]. Bei diesen Fällen tritt ein intrauteriner Fruchttod besonders häufig auf [4,6,7]. Auch eine gehäufte neonatale Azidoserate wird beobachtet [2,4].…”
Section: Zusammenfassungunclassified